2020 Vision: Envisioning a new generation of STEM learning research - Dierking, Lynn D.; Falk, John H. (Cultural Studies of Science Education, 2016)
In this issue, we have compiled six original papers, outcomes from the U.S. National Science Foundation (US-NSF)-funded REESE (Research and Evaluation on Education in Science and Engineering) 2020 Vision: The Next Generation of STEM Learning Research project. The purpose of 2020 Vision was to re-envision the questions and frameworks guiding STEM research in the twenty-first century, given that notions of learning have changed significantly in the last decade. The papers present diverse research principles that emerged from an initial 2020 Vision conference at Oregon State University (OSU), were then vetted more broadly with the science education community nationally and internationally, and presented in a public 2020 Vision symposium series also at OSU. Individually and as a group, these papers argue that if STEM learning is lifelong, life-wide and life-deep, research designs need to cut across the diverse settings and investigate the multiple contexts and media in which learners live and interact. Authors call for research paradigms that holistically reflect questions of the “what, when, where, why, how and with whom” of STEM learning. Associated Forum papers respond and expand the conversation by critically examining the recommended research principles and in some cases, challenging both authors and editors to think even more broadly. Two Key Contributor pieces highlight the contributions of researchers who have helped to push on these research boundaries, advancing science education research nationally and internationally. A final synthesis paper, a case study of research being conducted in a diverse, under-resourced community in Portland, Oregon provides one example of how the 2020 Vision research principles might be integrated into a comprehensive STEM learning research study.